(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
In this article, I describe how my behavior-analytic perspective on infant and child development evolved and what a behavior-analytic theory of development might look like. I begin by describing how my approach to teaching child development courses changed from focusing mostly on behavior analysis to teaching critical thinking skills that would enable students to evaluate traditional developmental research and theory and then to find a behavior-analytic perspective more appealing. I describe the critical thinking skills I teach students, including nominal fallacy, circular reasoning, reification, and parsimony. Throughout, I contrast a traditional developmental approach to research and theory with a behavior-analytic approach. In particular, I note differences between the between-subjects experimental designs used by developmental researchers and the within-subjects experimental designs used by behavior analysts in terms of internal and external validity and their implications for theory construction. I argue that, because behavior-analytic theory is inductively derived from decades of experimental analysis, it is in a better position to achieve the goals of prediction, control, and understanding and can generate successful technologies of behavior change.